Contextual influence, frailty and the spatial patterns of child mortality in Nigeria - Salau, Sulaiman (My University, 2011)
The main aim of the project is to investigate statistical models that account for the influence of contextual factors and frailty on Child Mortality (CM) and to investigate the spatial patterns of CM in Nigeria. Using data from the Nigerian Demographic and Health Survey, results from a descriptive investigation of clustering showed that clustering of child mortality exists at the household, community and state levels and these need to be taken into account in the multivariate analysis by the inclusion of frailty effects at the relevant levels. A total of 8 models were evaluated using geo-additive survival models and the results in Chapter 4 reveal that the inclusion of frailty terms as well as the inclusion of contextual variables at the community level lead to an improvement in the model fit, thereby suggesting the importance of contextual and frailty effects. A higher share of state level variability in the data was due to the structured spatial effect. Although, the spatial patterns were found to be insignificant, they point to very interesting patterns in child mortality variations.